Analysis of Leadership Style on Employee Performance with Job Satisfaction As A Moderation Variable - Arisanti, Dian; Soedarmanto, Soedarmanto; Purwanto, Edi (Jejaring Administrasi Publik, 2023)
The primary objective of this study is to examine the impact of leadership style, motivation, and remuneration on employee performance, with work satisfaction serving as a moderating variable. The research focuses specifically on employees of PT Pelindo Daya Sejahtera, PHC Surabaya Hospital unit. The study's population included a total of 105 personnel, all of whom were affiliated with PT Pelindo Daya Sejahtera, namely the PHC Surabaya Hospital unit. The research used a saturation sampling approach to choose a sample of 105 workers from PT Pelindo Daya Sejahtera and PHC Surabaya Hospital unit. The methodology used entails the utilization of multiple linear regression analysis. Based on the findings and subsequent discourse, it can be inferred that the variables of leadership style, motivation, and compensation exert a notable impact, while job satisfaction, as a moderating variable, enhances the influence on the employees of PT Pelindo Daya Sejahtera, PHC Surabaya Hospital unitKeywords: Leadership Style, Employee Performance, Job Satisfaction